2016
DOI: 10.1007/s10530-016-1117-2
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the efficacy of an aquatic invasive species prevention campaign among water recreationists

Abstract: Water recreationists regularly engage in behavior that can contribute to the spread of aquatic invasive species (AIS), which can result in costly consequences for managers. As AIS prevention is more cost-effective than response, educational campaigns are implemented as a preventative management strategy. However, little is known about the efficacy of education campaigns in promoting recreationists' knowledge, personal responsibility, and engagement in behaviors that can prevent AIS spread. This study explored … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
26
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(28 citation statements)
references
References 41 publications
1
26
0
Order By: Relevance
“…Surprisingly, substantial knowledge gaps were identified concerning the presence and prevention of non-native mussel transmission. In our study, awareness of eutrophication was found to be a simple but near-universal predictor of respondent's knowledge concerning AIS, while previous studies identified breadth and depth of recreational involvement as near-universal predictors (Eiswerth et al 2011;Seekamp et al 2016). Therefore, our study provides further evidence for the overall importance of lake-based activities and lake-related knowledge as determinants of AIS knowledge.…”
Section: Discussionsupporting
confidence: 56%
See 3 more Smart Citations
“…Surprisingly, substantial knowledge gaps were identified concerning the presence and prevention of non-native mussel transmission. In our study, awareness of eutrophication was found to be a simple but near-universal predictor of respondent's knowledge concerning AIS, while previous studies identified breadth and depth of recreational involvement as near-universal predictors (Eiswerth et al 2011;Seekamp et al 2016). Therefore, our study provides further evidence for the overall importance of lake-based activities and lake-related knowledge as determinants of AIS knowledge.…”
Section: Discussionsupporting
confidence: 56%
“…Inconsistent nature of the answers to the open-ended questions provides evidence that current outreach efforts are either not delivering the message in a clear, understandable manner or that it is not being retained. The message of 'clean, drain, dry' is a central tenant of invasive mussel prevention and control campaigns around the world (Gates 2009;Seekamp et al 2016;Zook and Phillips 2012), and needs to be delivered successfully to recreationists utilizing watercrafts to prevent mussel invasion. Even when water-craft users are willing to drain their boats, they are unlikely to use a hot water rinse as recommended (Connelly et al 2016;Seekamp et al 2016).…”
Section: Musselsmentioning
confidence: 99%
See 2 more Smart Citations
“…To obtain an effective reduction of the risk in the short term, current research indicates that proper bait disposal by anglers is crucial to avoid biological invasions of freshwater and estuarine ecosystems (Kilian et al., ). Because many anglers do not regard improper bait disposal as an undesirable behaviour, information campaigns about aquatic invasions should be a first step towards improving disposal behaviour (Seekamp et al., ; Sharp, Cleckner & DePillo, ; Shaw, Howell & Genskow, ), provided that increased awareness will be coupled with an increased availability of waste bins around water bodies and fishing ponds.…”
Section: Discussionmentioning
confidence: 99%